Developing students learning motivation in science experiments using mobile augmented reality - Gopalan, Valarmathie; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir (Science and Engineering Research Support Society, 2020)
With the advent of Mobile Augmented Reality (MAR) technology, it has the potential to be widely used in learning because of its ability to deliver the learning materials from multiple perspectives. This paper aims to propose a combination of concepts derived from the theory of animate vision, multimedia learning principles, constructivism learning theory and Attention, Relevant, Confidence, and Satisfaction (ARCS)motivation theory. This paper recommends the combination of these concepts for an exclusive mobile learning experience through the use of three-dimensional (3D) animated visualization. The literature review method is exploited to construct a state of the art theories and models. The combination of these concepts into the Mobile Augmented Reality (MAR) learning environment is expected to improve students’ learning motivation in science experiment. The results of this study are valuable for students, teachers, instructors and researchers interested in applying Mobile Augmented Reality in learning.